YTHDF1 Negatively Regulates Treponema pallidum-Induced Inflammation in THP-1 Macrophages by Promoting SOCS3 Translation in an m6A-Dependent Manner - Li, Zhijia; Teng, Muzhou; Jiang, Yinbo; Zhang, Litian; Luo, Xi; Liao, Yuhui; Yang, Bin (Frontiers in Immunology, 2022)
Background: Previous studies have confirmed that the bacterium Treponema pallidum (TP) or its proteins provide signals to macrophages that induce an inflammatory response; however, little is known about the negative regulation of this macrophage-mediated inflammatory response during syphilis infection or the underlying mechanism. Recent evidence suggests the role of the RNA modification, N6-adenosine methylation (m6A), in regulating the inflammatory response and pathogen-host cell interactions. Therefore, we hypothesized that m6A plays a role in the regulation of the inflammatory response in macrophages exposed to TP. Methods: We first assessed m6A levels in TP-infected macrophages differentiated from the human monocyte cell line THP-1. The binding and interaction between the m6A “writer” methyltransferase-like 3 (METTL3) or the m6A “reader” YT521-B homology (YTH) domain-containing protein YTHDF1 and the suppressor of cytokine signaling 3 (SOCS3), as a major regulator of the inflammatory response, were explored in differentiated TP-infected THP-1 cells as well as in secondary syphilitic lesions from patients. The mechanisms by which YTHDF1 and SOCS3 regulate the inflammatory response in macrophages were assessed. Results and Conclusion: After macrophages were stimulated by TP, YTHDF1 was upregulated in the cells. YTHDF1 was also upregulated in the syphilitic lesions compared to adjacent tissue in patients. YTHDF1 recognizes and binds to the m6A methylation site of SOCS3 mRNA, consequently promoting its translation, thereby inhibiting the JAK2/STAT3 pathway, and reducing the secretion of inflammatory factors, which results in anti-inflammatory regulation. This study provides the first demonstration of the role of m6A methylation in the pathological process of syphilis and further offers new insight into the pathogenesis of TP infection.